Pericytes on placental capillaries in terminal villi preferentially cover endothelial junctions in regions furthest away from the trophoblast. (15th January 2021) - Harris, Shelley E.; Matthews, Kate SH.; Palaiologou, Eleni; Tashev, Stanimir A.; Lofthouse, Emma M.; Pearson-Farr, Jennifer; Goggin, Patricia; Chatelet, David S.; Johnston, David A.; Jongen, Maaike SA.; Page, Anton M.; Cleal, Jane K.; et al.
Abstract: Introduction: Pericytes are a common feature in the placental microvasculature but their roles are not well understood. Pericytes may provide physical or endocrine support for endothelium and in some tissues mediate vasoconstriction. Methods: This study uses serial block-face scanning electron microscopy (SBFSEM) to generate three-dimensional (3D) reconstructions of placental pericytes of the terminal villi and transmission electron microscopy (TEM) to study pericyte endothelial cell interactions. The proportion of endothelial cell junctions covered by pericytes was determined. Results: The detailed 3D models of placental pericytes show pericyte structure at a new level of detail. Placental pericytes have many fingers extending from the cell body which can span multiple capillary branches. The proportion of endothelial cell-cell junctions covered by pericytes was significantly higher than pericyte coverage of capillary endothelium as a whole (endothelium: 14%, junctions: 43%, p < 0.0001). However, the proportion of endothelial cell-cell junctions covered by pericytes in regions adjacent to trophoblast was reduced compared to regions >3 μm away from trophoblast (27% vs 62% respectively, p < 0.001). No junctional complexes were observed connecting pericytes and endothelial cells but there were regions of cell membrane with features suggestive of intercellular adhesions. Discussion: These data suggest that the localisation of pericytes on the villous capillary is not random but organised in relation to both endothelial junctions and the location of adjacent trophoblast. This further suggests that pericyte coverage may favour capillary permeability in regions that are most important for exchange, but limit capillary permeability in other regions. Highlights: Three-dimensional imaging highlights the structure of placental pericytes. Placental pericytes preferentially cover endothelial junctions. The proportion of covered junctions decreased in regions adjacent to trophoblasts. The localisation of placental pericytes suggests endothelial coverage is non-random. Junction coverage may alter capillary permeability in key regions of exchange.